Determination of Anionic Detergent Concentration of Karasu Stream in Sinop (Turkey) - Ayşe Gündoğdu; Erdi Gültepe; Uğur Çarlı (Turkish Journal of Agriculture: Food Science and Technology)
The study was achieved between May 2014 and April 2015 at the Karasu Creek located in the province of Sinop. It was conducted to determine anionic detergent pollution and some physicochemical properties (pH, temperature, conductivity, salinity, dissolved oxygen, total hardness, chemical oxygen demand, phosphate PO4-3, total nitrogen). The anionic detergent concentration of the stations was determined on a monthly basis. Seasonally averaged values of the anionic detergent was measured as the highest value in the autumn season. The lowest values of anionic detergent were found in stations in winter and spring. The increase in the concentration of anionic detergent is caused by population growth in residential areas, increased agricultural activities and rains, and that chemicals move to riverbed from terrestrial areas with rain water.